Cytomegalovirus Hepatitis and Pancreatitis in the Immunocompetent - Chan, Aaron (the Academic Division of Ochsner Clinic Foundation, 2014)
BACKGROUND: Cytomegalovirus (CMV) is a double-stranded DNA virus and a member of the Herpesviridae family. It is a lytic virus that causes a cytopathic effect in vitro and in vivo. CMV affects nearly all humans, with a 60%-100% seroprevalence worldwide, and in the immunocompetent it typically manifests as a mild and self-limiting mononucleosis syndrome. In immunocompromised patients, CMV has the ability to cause significant inflammation in many different organ systems. CASE REPORT: We report an unusual case of hepatitis and pancreatitis secondary to CMV in an immunocompetent patient. A 29-year-old male was admitted with elevated lipase, elevated aminotransferases, and epigastric pain after an acute viral prodrome. An initial CMV DNA polymerase chain reaction workup was positive, indicating acute or reactivated infection. Liver histology was consistent with CMV infection. Magnetic resonance cholangiopancreatography, endoscopic ultrasound, and intraoperative cholangiogram were not indicative of other etiologies. CMV viremia was successfully cleared with ganciclovir, and the patient experienced clinical and biochemical improvements. CONCLUSION: Pancreatitis and hepatitis secondary to CMV are rare but should be considered in the workup of immunocompetent patients, especially in the presence of a recent viral-like illness.